Decreasing EFL learners’ intercultural communicative anxiety levels through a blended environment - Emrah Özdemir; Dinçay Köksal (Literacy Trek)
Language classes should focus not only on linguistic skills but also on developing essential cultural and intercultural competencies, as fostering intercultural communicative competence has become a key objective in modern foreign language education. In this context, blended learning environments that combine face-to-face classroom practices with technology-enhanced activities offer promising opportunities to reduce learners' intercultural communication anxiety. This study aimed to examine the effectiveness of blended intercultural instruction on English as a Foreign Language (EFL) learners’ intercultural communicative anxiety levels. A two-group quasi-experimental research design was employed, involving an in-class discussion group and an online discussion group. Data were gathered through a background questionnaire and the Intercultural Communicative Anxiety Scale (ICAN). Findings revealed that students in the online discussion group experienced a significantly greater reduction in intercultural communicative anxiety compared to those in the in-class discussion group. These results suggest that well-structured blended environments, which provide supportive and low-pressure contexts for interaction, can be effective in lowering anxiety and enhancing intercultural learning. Implications for language instruction and curriculum design are also discussed.